NANOMATERIALS FOR CATALYTIC CONVERTERS: IMPROVING AIR QUALITY THROUGH INNOVATION - Haruto Takahashi; Riko Kobayashi; Nisreen Al Sayid (Research of Scientia Naturalis, 2025)
Air pollution remains a critical global issue, largely due to emissions from vehicles. Catalytic converters play a vital role in reducing harmful pollutants, but their efficiency can be improved through innovative materials. Nanomaterials have emerged as promising candidates for enhancing catalytic converter performance. This study aims to investigate the application of nanomaterials in catalytic converters to improve their efficiency in reducing harmful emissions. The research focuses on identifying specific nanomaterials that can enhance catalytic activity and longevity. A comprehensive review of existing literature on nanomaterials used in catalytic converters was conducted. Laboratory experiments were performed to evaluate the catalytic performance of various nanomaterials, including metal nanoparticles and nanocomposites, in simulated exhaust conditions. Emission measurements were analyzed to assess effectiveness. Findings indicate that the incorporation of nanomaterials significantly enhances the catalytic activity of converters. Metal nanoparticles demonstrated improved oxidation and reduction reactions, resulting in higher conversion rates of NOx, CO, and unburned hydrocarbons. The study also identified optimal concentrations and combinations of nanomaterials for maximum efficiency. This research highlights the potential of nanomaterials to transform catalytic converters and improve air quality.